Slovenci u Varaždinu tijekom 1941. i 1942. godine - Huzjan, Vladimir (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2019)
In Croatian historiography not much has been written about the persecution of Slovenes and forced expatriation to the territory of the Independent State of Croatia during the World War II. The situation in Varaždin has been mentioned only by few sources. For the first time this paper lists 167 individuals and entire families who were provided with the domicile of the Town of Varaždin as the warranty of safety from the 13 November 1941 to the 13 June 1942. The analysis showed that the majority of the Slovenes, who were provided with the domicile, had lived in the town area or its immediate surroundings and worked in public or private sectors before the beginning of the World War II. For almost every person, the data on the exact time of stay was obtained and presented. It was determined that only a small number of civilians was forcibly displaced from Slovenia and provided with the domicile of the Town of Varaždin.
Keywords: NDH; Neodvisna država Hrvaška; Slovenci na Hrvaškem; Varaždin